Methodological Aspects of Valuation of Credit Institutions under External Uncertainty - A. A. Pomulev; N. S. Pomuleva (Финансы: теория и практика, 2022)
The article is devoted to the research of the issues of commercial bank business valuation under the conditions of uncertainty. The study aims to develop a model for forecasting the value of total assets and loan portfolio of a commercial bank within the framework of value estimation under external uncertainty. The relevance of the paper is that in the context of the COVID‑19 pandemic, military actions and sanctions pressure it is difficult to justify the market value of credit institutions due to the difficulties in implementing the methodology of assessment of banks whose business is associated with increased risks. The scientific novelty of the study lies in the development of a regression model that allows forecasting the value of total assets and the loan portfolio of a commercial bank as key value factors under external uncertainty. The authors used the following methods of scientific research: deduction, induction, correlation and regression analysis, and logical method. The key factors of business valuation of Russian banks are systematized. The authors propose to build a model within the framework of the income approach, based on the forecast of external cost factors: total assets and loan portfolio of the banking sector. A leading indicator that affects total assets and loan portfolio is justified. A model has been developed which makes it possible to forecast the total assets and loan portfolios of the banking sector and find the required value of the assets of the bank being evaluated through the market share. The model is tested on the example of the valuation of Sber. The authors conclude that the model developed by the authors makes it possible to build scenarios for future cash flows and quantify the valuation interval of a commercial bank. The prospect of further research is related to evaluating the influence of internal financial and non-financial factors in the context of the valuation management system. The article will be useful to practicing appraisers in business valuation and investors.